(untitled) (Economic and Political Thought, 2018)
The authors propose a method of assessment of efficiency of regional PES’s by selecting statistically significant inputs and outputs as well as the environmental variable. In the final DEA model variables which show the positive correlation and statistically significant relationships between input variables and outputs (effects) were selected. Among the environmental variables the one with the strongest relationships with output variables was chosen. For the purposes of the resource management assessment of PES’s an analysis of technical relative efficiency of two Polish provinces was conducted using the Data Envelopment Analysis (DEA) method. These provinces represent a different labour market situation as Podlaskie is one of the peripheral regions and Mazowieckie voivodeship has the best economic indicators in Poland. The analysis has shown that the environmental variable has a significant impact on PES performance (overall improvement in technical efficiency results). The results of the analysis also enabled the identification of benchmark PES’s, the identification of areas requiring improvement and the selection of changes that will contribute to improving efficiency more prominently than for other variables.